Edukasi Perawatan Diri sebagai Upaya Meningkatkan Kemandirian Lansia pada Peserta Sekolah Lansia Indonesia Ramah Lansia Jawa Barat (IRL Jabar) - Citra Cahyarini; Susiana Nugraha; Tri Suratmi; Laila Ulfa; Yuna Trisuci Aprillia (Universitas Respati Indonesia, 2026)
Background: The increasing older adult population in Indonesia has been accompanied by a higher prevalence of health problems affecting independence. One common issue is inadequate self-care practices, particularly in maintaining skin health, personal hygiene, and daily living activities. Poor self-care may increase the risk of health problems, reduce quality of life, and accelerate dependency. Community-based elderly schools provide an appropriate setting to improve knowledge and practical skills through continuous health education. Objective: This community service program aimed to improve older adults' knowledge and self-care skills to enhance independence among participants of the Indonesia Ramah Lansia Elderly School, West Java. Methods: The program employed a participatory health promotion approach through interactive lectures, demonstrations, group discussions, and practical self-care sessions. Educational materials covered self-care concepts, skin health maintenance, appropriate moisturizer use, and simple daily skin care practices. Knowledge was evaluated using pre-test and post-test questionnaires, while practical skills were assessed through direct observation. Results: Participants actively engaged in all educational activities and successfully demonstrated the recommended self-care practices. The program improved participants' knowledge and practical skills related to skin care, moisturizer application, and xerosis prevention. Participants also showed greater motivation to independently perform self-care activities in their daily lives. Conclusion: Community-based self-care education is an effective health promotion strategy to improve knowledge, practical skills, and independence among older adults. Sustainable educational programs through elderly schools are recommended to support healthy ageing and improve quality of life.